Rigor: An Essentiality in Qualitative Research - Shazia Qasim Jamshed; Mohamed Izham Mohamed Ibrahim; Mohamed Azmi Ahmad Hassali; Asrul Akmal Shafie; Mahmoud Sa'di Mohammad Al-Haddad; Ramadan Alkalami (University of Minnesota Libraries Publishing, 2010)
Type: Letter